A Model for Lifelong Learners' Educational Records and Identity in a Next Generation Learning Management System - Gerd Kortemeyer; Stefan Dröschler; Peter Riegler; Nick Koslowski (FernUniversität Hagen, 2021)
The need to be competitive in a fast-changing global job market will likely lead to an increased demand for "just-in-time" educational experiences. Parallel to developments in the medical sector with virtual patient records, the paper presents a model for storing and managing educational data gathered along a lifelong learning journey, such as transcripts, artifacts, and performance analytics. Using the concept of Social Linked Data ("SOLID"), the learners instead of the educational institutions would have sovereignty over their own data, while transactional fingerprints would be used to guarantee data integrity using a federated blockchain.